The Kaleidoscope Model of policy change: Applications to food security policy in Zambia. (September 2018) - Resnick, Danielle; Haggblade, Steven; Babu, Suresh; Hendriks, Sheryl L.; Mather, David
Highlights: Argues that achieving policy impact depends on understanding policy processes. Builds on existing work to derive the Kaleidoscope Model (KM) of policy change. Tests the KM on episodes of agriculture and micronutrient policy reform in Zambia. Provides three additional tools for analyzing policy systems and outcomes. Offers measurement criteria to promote replicability and refinements by others. Abstract: What drives policy reform after long periods of policy inertia? What factors shape the effectiveness of policy implementation following reform decisions? These questions increasingly concern the international donor and research communities, given the importance of policy environments in shaping development outcomes and the growing need to achieve development impact with scarce resources. To address these questions, this paper introduces the Kaleidoscope Model of policy change. Inductively derived from empirical examples in developing countries, political economy literature, and theoretical scholarship on the policy process, the model proposes a set of 16 operational hypotheses to identify the conditions under which policies emerge on the agenda and ultimately are implemented. The paper tests the model empirically in Zambia by evaluating eight policy reform episodes related to agricultural input subsidies and vitamin A fortification. Empirical application and hypothesis testing rely on rigorous process tracing using secondary sources and semi-structured interviews with a purposive sample of 58 stakeholders in Zambia. In the policy reforms studied, a majority of the KM's core variables proved robust across the two distinct policy domains, while a handful emerged as relevant only episodically. In an era of growing pressure on donor resources and government budgets, the Kaleidoscope Model offers a practical framework through which practitioners and researchers can assess when and where investments in policy reforms are most feasible given a country's underlying political, economic, and institutional characteristics.